THE EFFECT OF HEIGHT OF TAPPING COVER AND SEED DRYING THICKNESS ON SIPERKASA FLOOR INNOVATION ON SEED QUALITY AND GROWTH OF RICE SEEDS (Oryza sativa L.) - Bagas Danurwenda Atmaja; Supono Budi Sutoto; Darban Haryanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2021)
Drying rice grain is one of the problems faced during the rainy season. This study aims to obtain information about the height of the tent, the thickness of the appropriate seed layer, and the interaction between the height of the tent and the thickness of the seed layer on the quality of rice seeds. The research method used is a field experiment prepared with a completely randomized block design using a split-plot design. As the main plot is the treatment of the height of the tarpaulin cover are 50, 80, and 110 cm. As a subplot is a thick layer treatment is 5, 7, 9, and 11 cm. Each treatment combination was repeated three times. The results showed that tarpaulin height has a significant effect on the parameters of the maximum growth potency and plant height at week 4. A tent height of 50 cm had the highest maximum growth potential. Layer thickness gave a significant effect on the parameters of the number of tillers at week 4 and plant height at week 4. The number of tillers in the fourth week of treatment with a layer thickness of 7, 9, and 11 cm was not significantly different but was significantly better than the layer thickness of 5 cm. The highest parameter of plant height at week 4 was 7 cm thick. There was an interaction between tarpaulin height and layer thickness on the parameters of the number of tillers at week 6, plant height at week 2 and 6.